2017
DOI: 10.1002/cctc.201601076
|View full text |Cite
|
Sign up to set email alerts
|

Dehydration of 2‐Octanol over Ca‐doped CeO2 Catalysts

Abstract: Vapor‐phase catalytic dehydration of 2‐octanol was investigated over Ca‐doped CeO2 at 375 °C and atmospheric pressure. Ca doping up to 0.15 wt % was found to increase the dehydration activity for 2‐octanol, whereas further increases in Ca content (0.50 and 1.25 wt %) detrimentally affected the conversion. Catalyst surface area and pore volume increased with increasing Ca content in Ca‐doped CeO2. Hydrogen temperature‐programmed reduction (TPR) profiles indicate that the partially reduced state of surface ceria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 46 publications
1
10
0
Order By: Relevance
“…The trend continues as the concentration of Ca increases, which is consistent with previous observations. [ 27,30 ] This change is due to the larger ionic radius of Ca 2+ (1.12 Å) than Ce 4+ (0.97 Å). [ 21 ] The doping level can also affect the morphology of Ca–CeO 2 nanotubes.…”
Section: Resultsmentioning
confidence: 99%
“…The trend continues as the concentration of Ca increases, which is consistent with previous observations. [ 27,30 ] This change is due to the larger ionic radius of Ca 2+ (1.12 Å) than Ce 4+ (0.97 Å). [ 21 ] The doping level can also affect the morphology of Ca–CeO 2 nanotubes.…”
Section: Resultsmentioning
confidence: 99%
“…have shown the advantages of CeO 2 ‐SiO 2 and CeO 2 ‐ZrO 2 binary oxides on the conversion and selectivity for dehydration of 4‐methylpentan‐2‐ol than CeO 2 alone. More recently, we investigated the effect of calcium doping on CeO 2 for the dehydration of 2‐octanol and we found that the partial surface reduction of CeO 2 was enhanced by the addition of calcium, which improved its dehydration activity for 2‐octanol . In the present work, we report on the effect of Ga and In addition to CeO 2 on the activity and product selectivity for dehydration of 1,5‐ and 2,4‐ pentanediol.…”
Section: Introductionmentioning
confidence: 65%
“…It is therefore a promising candidate material for photocatalytic degradation of deleterious organic pollutants. Previous studies have shown that morphology and size control, doping of various metal ions, and heterojunction coupling are three common strategies for enhancing the photocatalytic performance of CeO 2 ‐based materials . The morphology of CeO 2 plays a major role in its photocatalytic performance, and our research group has successfully fabricated a series of high‐performance CeO 2 photocatalysts with different morphologies and superior performances including porous broom‐like, hedgehog‐like, confeito‐like and hollow octahedral structures .…”
Section: Introductionmentioning
confidence: 95%
“…Cerium dioxide (CeO 2 ) is one of the most important rare earth metal oxides, and it has attracted much attention due to its excellent properties such as low toxicity, high degree of chemical stability, safety and resistance to photocorrosion primarily . It has various applications including applications as UV blockers, polishing materials, photocatalysts, electrolytes, sensors and fuel cells . In addition, the photocatalytic properties of CeO 2 are similar with those of TiO 2 ‐based materials including a wide band gap (2.90 eV) and strong absorption in the UV region.…”
Section: Introductionmentioning
confidence: 98%